Práticas pedagógicas nos anos finais do ensino fundamental da matemática no contexto da pandemia no período de 2020 a 2021 - Peruzzo, Fernanda (My University, 2022)
We present results of a study whose objective was to identify the pedagogical practices developed in the area of Mathematics, in Elementary School, Final Years, in the context of the pandemic. To this end, a theoretical framework was built articulating concepts related to the theme, including studies, mapping the challenges and advances in pedagogical practices, during the pandemic period. The corpus of the research was built from the transcripts of semi-structured and dialogued interviews carried out with four Mathematics teachers from the Final Years of Elementary School in municipal schools in a municipality in Serra Gaúcha. The focus was on listening to the participants about how their practices occurred in the face of the pandemic scenario: good experiences, student involvement, technological resources, among other aspects. The constructed data were analyzed and discussed based on discursive textual analysis, guided by recommendations arising from studies on the subject, which generated three emerging categories: difficulties, oriented studies and the contextualization of Mathematics teaching. The results indicate that, given the moment experienced in the pandemic, one of the solutions found for classes to continue, without harming the school year, was the implementation of the Emergency Remote Teaching modality, in accordance with the opinions of the National Council of Education. Faced with the situation, one of the pedagogical strategies used during the pandemic was synchronous classes, which made it possible to develop activities related to learning. For the development of this modality, it was necessary to use digital tools such as WhatsApp®, Google Meet®, Google Classroom®, among other resources. The help of technologies was very important at the time, but difficulties arose regarding the use of these technological resources, such as: problems with internet access, difficulty in using digital tools and the lack of equipment such as a computer, cell phone and others that were necessary. To minimize the difficulties faced, another strategy that was designed to help organize the studies was the study scripts, with guidelines so that the students could develop the proposed activities. We can also infer that among the challenges and anxieties experienced at the time, the teacher had an essential role in reorganizing the teaching and learning process, given the demands and guidelines. We also highlight that the school needed to welcome the students and their families, given the anxieties and demands of the moment. Technology represents resources that can help in educational practice, but it is necessary to provide adequate teacher training so that teachers can continually re-dimension their practice. [resumo fornecido pelo autor]
Apresentamos resultados de um estudo cujo objetivo foi o de identificar as práticas pedagógicas desenvolvidas na área da Matemática, no Ensino Fundamental, Anos Finais, no contexto da pandemia. Para tanto, foi construído um quadro teórico articulando conceitos relacionados à temática, incluindo estudos, mapeando os desafios e os avanços das práticas pedagógicas, no período da pandemia. O corpus da pesquisa foi construído a partir das transcrições de entrevistas semiestruturadas e dialogadas realizadas com quatro professoras de Matemática dos Anos Finais do Ensino Fundamental das escolas da rede municipal de um município da Serra Gaúcha. O foco foi ouvir as participantes sobre como ocorreram suas práticas diante do cenário pandêmico: as boas experiências, o envolvimento dos alunos, os recursos tecnológicos, dentre outros aspectos. Os dados construídos foram analisados e discutidos a partir da análise textual discursiva, tendo como norteadores de análise recomendações advindas de estudos sobre o tema, que geraram três categorias emergentes: dificuldades, estudos orientados e a contextualização do ensino da Matemática. Os resultados indicam que, diante do momento vivenciado na pandemia, uma das soluções encontrada para que as aulas continuassem, sem prejudicar o ano letivo, foi a implantação da modalidade do Ensino Remoto Emergencial, conforme os pareceres do Conselho Nacional de Educação. Frente à situação, uma das estratégias pedagógicas utilizada para o momento pandêmico foram as aulas síncronas, que possibilitavam desenvolver atividades relacionadas à aprendizagem. Para o desenvolvimento dessa modalidade foram necessários o uso de ferramentas digitais como WhatsApp®, Google Meet®, Google Classroom®, entre outros recursos. O auxílio das tecnologias foi muito importante para o momento, mas surgiram dificuldades referentes ao uso desses recursos tecnológicos, como: problemas com o acesso à internet, dificuldade na utilização das ferramentas digitais e a falta de equipamentos como computador, celular e outros que fossem necessários. Para minimizar as dificuldades enfrentadas, outra estratégia que foi pensada para auxiliar na organização dos estudos foram os roteiros de estudos, com orientações para que os alunos pudessem desenvolver as atividades propostas. Podemos, ainda, inferir que dentre os desafios e anseios vivenciados pelo momento, o professor teve uma função essencial de reorganizar o processo de ensino e aprendizagem, diante das demandas e orientações. Destacamos, também, que a escola precisou acolher os alunos e seus familiares, diante das angústias e demandas do momento. A tecnologia representa recursos que podem auxiliar na prática educativa, mas é preciso que seja possibilitada formação docente adequada para que o professor redimensione continuamente sua prática. [resumo fornecido pelo autor]
Keywords: Matemática (Ensino fundamental); Prática de ensino; Ensino auxiliado por computador; Ensino à distância; Pandemias; Mathematics (elementary school); Student teaching; Computer-assisted instruction; Distance education; Pandémies